Brain deletion of insulin receptor substrate 2 disrupts hippocampal synaptic plasticity and metaplasticity. - Derek A Costello; Marc Claret; Hind Al-Qassab; Florian Plattner; Elaine E Irvine; Agharul I Choudhury; K Peter Giese; Dominic J Withers; Paola Pedarzani (PLoS ONE)
Objective Diabetes mellitus is associated with cognitive deficits and an increased risk of dementia, particularly in the elderly. These deficits and the corresponding neurophysiological structural and functional alterations are linked to both metabolic and vascular changes, related to chronic hyperglycaemia, but probably also defects in insulin action in the brain. To elucidate the specific role of brain insulin signalling in neuronal functions that are relevant for cognitive processes we have investigated the behaviour of neurons and synaptic plasticity in the hippocampus of mice lacking the insulin receptor substrate protein 2 (IRS-2). Research design and methods To study neuronal function and synaptic plasticity in the absence of confounding factors such as hyperglycaemia, we used a mouse model with a central nervous system- (CNS)-restricted deletion of IRS-2 (NesCreIrs2KO). Results We report a deficit in NMDA receptor-dependent synaptic plasticity in the hippocampus of NesCreIrs2KO mice, with a concomitant loss of metaplasticity, the modulation of synaptic plasticity by the previous activity of a synapse. These plasticity changes are associated with reduced basal phosphorylation of the NMDA receptor subunit NR1 and of downstream targets of the PI3K pathway, the protein kinases Akt and GSK-3β. Conclusions These findings reveal molecular and cellular mechanisms that might underlie cognitive deficits linked to specific defects of neuronal insulin signalling.